Case Study of Cybercrime Implementation in Technology Development - Albed Maulana; Deitje Pongoh; Fanny Jouke Doringin; Roby Stevi Lumbu; Yehuda Yura; Hizkia Rampi; Dennis Timpua; Junior Assa; Chievo Simoboh (Interdisciplinary Journal of Advanced Research and Innovation, 2024)
The relentless march of modern technology has undeniably ushered convenience, comfort, and efficiency into various facets of our lives. However, accompanying these technological strides are the looming threats of cybercrime. This article extensively reviews a case study illustrating the implementation of cybercrime within the context of technological progress, meticulously examining its far-reaching impact. Rigorous research is conducted to unravel the intricacies of this case, offering detailed insights into the ongoing efforts to counteract its effects. In today's digital age, cybercrime stands as a formidable and rapidly expanding menace, casting a shadow over critical infrastructure, sensitive data, and organizational stability. Our investigation delves into the profound influence of technological developments on the emergence of diverse cyberattacks and hacking incidents. Be the pivotal roles of proactive monitoring and comprehensive security awareness training. This study advocates for a heightened state of vigilance and underscores the necessity of adopting preemptive measures to navigate the evolving landscape of cyber threats successfully. The quest for effective cybersecurity is portrayed as an ongoing and dynamic endeavor, demanding adaptability and a holistic approach to fortify against the relentless evolution of digital risks.